Towards a Joint Characterization of Monetary Policy and the Dynamics of the Term Structure of Interest Rates - Ralf Fendel (Deutsche Bundesbank, 2004)
The paper develops an empirical no-arbitrage Gaussian affine term structure model to explain the dynamics of the German term structure of interest rates from 1979 through 1998. In contrast to most affine term structure models two risk factors that drive the dynamics are linked to observable macroeconomics factors: output and inflation. The results obtained by a Kalman-filter-based maximum likelihood procedure indicate that the dynamics of the German term structure of interest rates can be sufficiently explained by expected variations in those macroeconomic factors plus an additional unobservable factor. Furthermore, we are able to extract a monetary policy reaction function within this no-arbitrage model of the term structure that closely resembles the empirical reaction functions that are based on the dynamics of the short rate only.
Keywords: E58; E43; G12; 330; affine term structure models; monetary policy rules; Kalman filter; Zinsstrukturtheorie; Zinsstruktur; Volatilität; Geldpolitik; Regelgebundene Politik; Reaktionsfunktion; Schätzung; Deutschland